Study on mass customisation of pagers in Singapore. - Koh, Kim Lin. (2008)
This study explored the acceptance of mass customisation of pagers in Singapore. The critical determinants for the successful implementation of mass customisation of pagers and the potential target segments for the customised pagers were identified. The research framework was developed based on the assertion that the use of mass customisation as a business strategy can arrest or reverse the declining trend for paging penetration rate. Results obtained from the research were used to forecast the pager penetration rate for the year 2000 and to examine the effects of customisation on this rate.